Intimately about death. Dying, mourning, and memory in the memoirs and correspondence of the Doliński/Łazarowicz family (Requiem, 2025)
A characteristic feature of 19th century personal documentary literature was the emphasis on descriptions of the last moments of loved ones’ lives. An interesting testimony to death and dying, can be found in the private correspondence, notes, and memoirs of the Doliński/ Łazarowicz family – a family of civil servants. The documentation preserved in the Lithuanian State Historical Archives in Vilnius, spanning nearly 60 years, reveals attitudes toward the death of loved ones, highlights strategies for coping with the sense of loss, and allows for the reconstruction of the emotional states experienced in connection with illness and dying. The aim of this article is to analyze the records documenting the deaths of close family members and to reflect on the function of these types of writings.